Production of value-added liquid fuel via microwave co-pyrolysis of used frying oil and plastic waste - Wan Adibah, Wan Mahari; Chong, Cheng Tung; Cheng, C. K.; Lee, Chern Leing; Hendrata, Kristian; Yek, Peter Nai Yuh; Ma, Nyuk Ling; Lam, Su Shiung (Elsevier Ltd, 2018)
The production of household wastes such as used frying oil (UFO) and plastic waste (PW) are increasing each year, thus representing potential feedstocks for conversion into an energy source. Microwave co-pyrolysis was investigated for its potential to transform a mixture of UFO and polyolefinic-based plastic waste into fuel product with desirable properties. The co-pyrolysis approach demonstrated positive synergistic effects in providing fast heating rate (up to 50 °C/min) and a lower reaction time (≤25 min), and generated up to 81 wt.% yield of liquid oil and 18 wt.% yield of pyrolysis gases for use as potential fuels. The liquid oil showed promising green properties comprising low oxygen content, free of nitrogen and sulphur and higher energy content (42–46 MJ/kg). The oil product also demonstrated improved stability and desirable fuel properties nearly similar to transport-grade diesel, thus indicating the great potential of microwave co-pyrolysis as an approach for transforming household wastes into value-added liquid fuel.